Analisis Pengaruh Tingkat Pendidikan dan Motivasi Kerja Terhadap Kesejahteraan Masyarakat di Kenagarian Sungai Naniang Kabupaten Lima Puluh Kota - Refilda Refilda; Jon Kanedi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research is motivated by the fact that the Kenagarian Sungai Naniang community is still not fully experiencing prosperity. Even though the people of Kenagarian Sungai Naniang have sufficient education and very high work motivation, the income they receive is still not sufficient to achieve prosperity. With the education and high work motivation obtained by the community, the community should be able to provide a bridge to get work easily and decently. The aim of this research is to find out how much influence the level of education and work motivation has on the welfare of the Kenagarian Sungai Naniang community. This research uses Quantitative Research methods. Data collected using questionnaire techniques. Respondents in this study were 283 people taken from a population of 3,121 people. The data analysis technique used is a multiple linear regression technique using SPSS. The conclusion is that education and work motivation have a very significant influence on welfare. The results of this research are the determinant coefficient test with a correlation coefficient value of 0.352 and an adjusted Rsquare value of 0.117, so the influence of X is 11.7%.